Challenges to the Acquisition of Literacy in Rural Primary Schools in Northern Uganda - Ssentanda, Medadi; Asiimwe, Allen (Informa UK Limited, 2020)
Literacy in the early years is crucial but attained amidst various challenges, especially in the Global South. Based on fieldwork conducted in October 2018 in four primary schools in Gulu district, Acoli region, northern Uganda, this study investigates school characteristics and facilities available to learners and teachers to scaffold the acquisition of literacy in the early years of schooling. These are discussed within the framework of Uganda’s mother-tongue education programme with a focus on the challenges of literacy acquisition. Data were collected from four schools by means of questionnaires, classroom interactions, and interviews, and were analysed through triangulation. The findings suggest that there are difficulties to attaining literacy within the MT education programme. Some of the challenges relate to teachers’ attitudes and practices, lack of school materials, poor school conditions, and large learner numbers per class. The implications of the observed challenges to literacy acquisition are discussed.